Statistical modelling and optimization of TIG welding process parameters using Taguchi’s method - Omprakasam, S. (Strojniški vestnik, 2022)
This current research focuses on optimizing the welding process parameters and penetration of 5052 alloys using a TIG welding process based on the Taguchi methods. Process parameters such as current, voltage, and speed with three different levels were taken to form the L27 orthogonal array using the design of experiments. Analysis of variance, signal-to-noise ratio analysis, and regression analysis were performed. The regression analysis indicated that the developed model has greater adequacy in predicting the reinforcement form factor (RFF), penetration shape factor (PSF) and hardness of the weld specimens. In addition, the optimized parametric condition for the welded specimen was found to be current, voltage, and speed of 140 A, 18 V, and 300 mm/min, respectively.
Keywords: 5052 alloys; aluminij; aluminium; faktor oblike ojačitve; faktor oblike prevaritve; hardness; metoda Taguchi; penetration shape factor; reinforcement form factor; Taguchi methods; TIG varjenje; TIG welding; trdota; zlitina AA5052